Novel non-terminal tumor sampling procedure using fine needle aspiration supports immuno-oncology biomarker discovery in preclinical mouse models. Issue 6 (18th June 2021) - Sitnikova, Suzanne Isabelle; Munnings-Tomes, Sophie; Galvani, Elena; Kentner, Stacy; Mulgrew, Kathy; Rands, Chris; España Agustí, Judit; Zhang, Tianhui; Ilieva, Kristina M; Rosignoli, Guglielmo; Ghadially, Hormas; Robinson, Matthew J; et al.
Abstract : Background: Immuno-oncology therapies are now part of the standard of care for cancer in many indications. However, durable objective responses remain limited to a subset of patients. As such, there is a critical need to identify biomarkers that can predict or enrich for treatment response. So far, the majority of putative biomarkers consist of features of the tumor microenvironment (TME). However, in preclinical mouse models, the collection of tumor tissue for this type of analysis is a terminal procedure, obviating the ability to directly link potential biomarkers to long-term treatment outcomes. Methods: To address this, we developed and validated a novel non-terminal tumor sampling method to enable biopsy of the TME in mouse models based on fine needle aspiration. Results: We show that this technique enables repeated in-life sampling of subcutaneous flank tumors and yields sufficient material to support downstream analyses of tumor-infiltrating immune cells using methods such as flow cytometry and single-cell transcriptomics. Moreover, using this technique we demonstrate that we can link TME biomarkers to treatment response outcomes, which is not possible using the current method of terminal tumor sampling. Conclusion: Thus, this minimally invasive technique is an important refinement for the pharmacodynamic analysis of the TME facilitating paired evaluation of treatment response biomarkers with outcomes and reducing the number of animals used in preclinical research.